Development of a Cr(VI) metal ion detection sensor using a modified pencil lead electrode (PLE) with a silver thin layer using the voltammetry method - Nella Aulia Putri; Trisna Kumala Sari; Budhi Oktavia; Sherly Kasuma Warda Ningsih (Acta Chimica Asiana, 2026)
Chromium(VI) metal ions have harmful effects on the environment and organisms. Chromium(VI) particles can cause chromosomal abnormalities, cross-linking, disruption of the cell cycle, and DNA damage within cells. Therefore, due to its high toxicity, it is crucial to monitor the concentration of chromium(VI) metal ions in the environment. This study aims to detect Cr(VI) metal ions in a simple, rapid, and effective manner. Electrochemical methods are employed to investigate the performance of PLE and Ag/PLE electrodes and to determine the optimal conditions for electrodeposition cycles and supporting electrolyte concentrations in detecting Cr(VI) metal ions. The electrochemical method is based on the specific reaction of the analyte, which generates an electrical signal. The PLE surface is modified with a silver thin layer through electrodeposition using cyclic voltammetry. The silver thin layer used for electrode modification offers several advantages, including improved electron transport and enhanced electrocatalytic response. The results indicate that the performance of Ag/PLE is superior to that of PLE in detecting Cr(VI) metal ions under optimal supporting electrolyte conditions, specifically 0.1 M HNO₃ with one electrodeposition cycle. Calibration curve analysis for Cr(VI) ions yielded the regression equation y = 0.6688x + 0.0085, with a correlation coefficient (R²) of 0.9958 and a limit of detection (LOD) of 0.18 mM.